Discriminant analysis of the sets won and the sets lost by one team in A1 Italian volleyball league - A case study - Marelic, N.; Resetar, T.; Jankovic, V. (Kinesiology, 2004)
Chain of factors determines success or failure in any sport match, but the measurable part of it is related to the indicators of efficient performance of technical-tactical elements or game phases during the matches. The sample consisting of 76 sets, obtained from 20 matches played by one team in Italian men's A1 league, was used in this study to determine, on the basis of five play-specific situational parameters, the differences between the sets won and the sets lost. A discriminant analysis was used. The canonical discriminant function significantly differentiated between the sets won and the sets lost, at the level of significance p<0.00. The discriminant function was defined by the highest projection of the variable spike in the phase of attack, and by somewhat lower projections of the variables spike in the phase of counterattack, serve reception, block and serve.